2014
DOI: 10.1371/journal.pone.0097833
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of MRSA and of Clinical Staphylococcus aureus Isolates from Iaşi, Romania

Abstract: Romania is one of the countries with the highest prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in the world. To obtain data on affiliation of MRSA to strains and clonal complexes and on the population of methicillin susceptible S. aureus (MSSA), clinical isolates from bloodstream infections, skin and soft tissue infections as well as from screening swabs were collected at hospitals in Ia?i, a city in the North-Eastern part of Romania. Isolates were characterised by microarray hybridisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 42 publications
6
33
0
Order By: Relevance
“…Most of them were pvl positive with pronounced genetic diversity (Tables S1 and S2; Figs 1 and 2). SSTIs caused by pvl positive CC121 methicillin-susceptible S. aureus (MSSA) were reported from Poland, Romania, Germany, Russia, Ireland, and United Kingdom, showing worldwide distribution of this lineage (25,26,30,33,34). In our study, CC121 was rare among healthy carriers.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Most of them were pvl positive with pronounced genetic diversity (Tables S1 and S2; Figs 1 and 2). SSTIs caused by pvl positive CC121 methicillin-susceptible S. aureus (MSSA) were reported from Poland, Romania, Germany, Russia, Ireland, and United Kingdom, showing worldwide distribution of this lineage (25,26,30,33,34). In our study, CC121 was rare among healthy carriers.…”
Section: Discussionmentioning
confidence: 57%
“…We have also found that MRSA was a rare cause of SSTIs in the targeted population (2.8%) which correlates well with results from studies from Poland (1.3%), Germany (3.0%), United Kingdom (1.8%), and Ireland (5.0%); low prevalence was also reported from China (4.0%) (25)(26)(27)(28). MRSA prevalence among SSTI strains between 5 and 10% was reported from France and Portugal, whereas some countries reported prevalence of over 25% (Russia, India, USA) and even over 50% (Romania) (27,(29)(30)(31)(32)(33). The majority of S. aureus isolates in our study belonged to seven major CCs (CC7, CC15, CC22, CC30, CC34, CC45, and CC121).…”
Section: Discussionmentioning
confidence: 99%
“…A strain that closely resembled the MRSA from rooks was frequently found among humans in Romania [116]. …”
Section: Resultsmentioning
confidence: 99%
“…e ., goats and sheep [2,3,154], but also in domestic pigs [123], cats, dogs, [156], cattle [155] and donkeys [157]. It could have been transmitted from wild to domestic ruminants, or vice versa , and the few reported human cases [116] could be related to contact to animals or animal products.…”
Section: Resultsmentioning
confidence: 99%
“…Ten Romanian CC1-MRSA-IV isolates were recovered between 2007 and 2010, during routine microbiological diagnostics in the Sfanta Parascheva Hospital for Infectious Diseases in Iasi, a 300-bed tertiary centre in North-Eastern Romania, where European CC1-MRSA-IV appears to be common (17).…”
Section: Additional Cc1-mrsa-iv Isolates Investigatedmentioning
confidence: 99%